Post-Transplant Erythrocytosis after Kidney Transplantation: Incidence, Risk Factors, Clinical Outcomes, and Therapeutic Approaches in 97 Adult Recipients - Ubaid Ur Rahman, Sami-Ur-Rahman, Khawar Suliman, Arshad Mahmood, Saif Ullah, Muhammad Mubbashar Nazar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Post-transplant erythrocytosis (PTE) is a clinically important complication after kidney transplantation, characterized by persistently elevated hemoglobin and/or hematocrit levels. It may increase the risk of thromboembolic complications and requires timely recognition and management. Objective: This study aimed to determine the incidence, risk factors, clinical outcomes, and therapeutic approaches for post-transplant erythrocytosis among adult kidney transplant recipients. Methods: An observational cross-sectional study was conducted at Begum Akhtar Rukhsana Memorial Trust and Safari Hospital, Rawalpindi. A total of 97 adult kidney transplant recipients who had completed at least six months of post-transplant follow-up were included. Demographic, clinical, transplant-related, and laboratory data were collected from medical records and transplant registries. Patients were categorized into PTE and non-PTE groups. Statistical analysis was performed using SPSS, including group comparisons and logistic regression to identify independent predictors of PTE. Results: Post-transplant erythrocytosis occurred in 21 out of 97 patients, giving an incidence of 22%. Patients with PTE had significantly higher hemoglobin, hematocrit, and post-transplant eGFR compared with non-PTE patients. Logistic regression identified male sex, living donor transplantation, and eGFR >60 mL/min/1.73 m² as independent predictors of PTE. Among patients with PTE, 13% developed thromboembolic events, including deep vein thrombosis and renal vein thrombosis. Therapeutic interventions included phlebotomy in 62% of patients and ACE inhibitor or ARB therapy in 38%, with clinical response observed in all treated patients. Conclusion: PTE remains a clinically relevant complication after kidney transplantation, particularly among male recipients, patients receiving living donor grafts, and those with preserved graft function. Regular monitoring of hematologic parameters, early diagnosis, and timely treatment with phlebotomy or ACE inhibitor/ARB therapy may help reduce thromboembolic risk and improve post-transplant outcomes. Keywords: Post-transplant erythrocytosis, kidney transplantation, hemoglobin, hematocrit, graft function, thromboembolism, phlebotomy, ACE inhibitors.